(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The demand for data in the 4G (Fourth Generation networks) and 5G (Fifth Generation networks) is becoming excessively high and the solution is being investigated to effectively utilize the available spectrum at the physical layer across different protocols to speed-up access from 2.5 to 10 times. Furthermore, the current proposals for 5G systems is envisaged to increase spectrum efficiency which brings about customer satisfaction, network density and operational efficiency, using newly 3.5 GHz NCC auctioned spectrum bands. The CPU processing power and cloud computing are expected to be the key driving factors in the evolution of wireless Network from 1G to 5G. These support wide range of new technologies like IoT, smart cities and Cyber and information Security as well as broadband penetration using entirely new Network architectural concept as a total transformation. This paper presents 5G network tariff implementation strategies and proposes a model of revenue generation which would enable a market mechanism that would allow the customer to communicate with the 5G Network and negotiate a contract based on some QoS (Quality of Service) parameters like blocking probabilities of High Priority Users (HPUs) and Low Priority Users (LPUs) , delay, and price. The percentage Improvement in Cumulative Revenue (CR) generated by the proposed model over the existing models is 10. Recommendations were made on the way forward for the optimum 5G tariffs in the Nigerian context